Misconceptions of the 6th Grade Elementary School Science Textbook - Maknun, Lu'luul; Dewi, Atika; Fakhriyah, Fina; Ratnasari, Yuni (Universitas Negeri Semarang, 2025)
Science learning is learning that contains many concepts so that there is the potential for misconceptions to occur in the learning process. Science misconceptions do not only occur in students and teachers, but also in textbooks that are used as learning materials. This study aims to identify science concepts that contain misconceptions in the IPAS grade VI book. Qualitative description using a content analysis approach was used as a method to analyze the concepts presented in the grade VI IPAS book. The data analysis technique uses a reference to five types of misconceptions, namely misidentifications, oversimplifications, overgeneralizations, undergeneralizations, and obsolete concepts and terms. The results of this study revealed the existence of misconceptions found in four chapters related to science material in the IPAS grade VI book. The seven misconceptions that were found consisted of two misconceptions of overgeneralizations and five misconceptions of oversimplifications.